Tools and graphics devices for the understanding and the interpretation of urban areas The Pianta Grande di Roma by Giovanni Battista Nolli - De Sanctis, Aldo (DISEGNARECON, 2014)
The techniques of representation and measurement always lead changes, both in the survey and the design activities, but especially induce changes in the way of thinking at the disciplines of survey and design and the educational choices that will knead the action. In the mid-eighteenth century, the updating and the diffusion of the "plane table" - with the orthogonal representation that follows - it promotes a radical change in the way of seeing the city, analyze and tell its wonder. The operational capabilities of the new instrument and the abstraction of orthogonal figuration promote, in other words, entirely new graphics devices and interpretative cares and, with these, a remarkable change in how to detect and read the determinants of urban areas.